A promising hybrid counter electrode of vanadium sulfide decorated with carbon nanotubes for efficient dye-sensitized solar cells. (June 2017) - Yue, Gentian; Liu, Xianqing; Mao, Yangfan; Zheng, Haiwu; Zhang, Weifeng
Abstract: A hybrid counter electrode (CE) of vanadium sulfide decorated with carbon nanotubes (CNTs/VS2 ) for efficient dye-sensitized solar cells (DSSCs) was prepared by using an in situ hydrothermal route, and the DSSC based on the CNTs/VS2 CE prepared at 180 °C and contained 0.05 g CNTs exhibits a power conversion efficiency of 7.72% under illumination of 100 mW cm −2 . The surface morphology of the VS2 and CNTs/VS2 changed from nanoparticles to one-dimensional (1D) structure was significantly affected by temperature. The electrochemical performance analyses including cyclic voltammetry, electrochemical impedance and Tafel curves for the CNTs/VS2 CEs with different temperatures and CNT contents reveal that the CNTs/VS2 CE possesses the better electrocatalytic activity and lower charge transfer resistance at the electrolyte|CE interface for I − /I3 − liquid electrolyte at 180 °C and 0.05 g CNTs. Graphical abstract: Much higher photovoltaic performance of dye-sensitized solar cell with CNTs/VS2 counter electrode as well as that of Pt configuration device. Highlights: The CNTs/VS2 composite were first time prepared and served as counter electrode (CE) for Pt-free DSSC. The CNTs/VS2 CE showed perfect electrocatalytic ability for I – /I3 – electrolyte. The power conversion efficiency of the DSSC reached 8.02% based on the CNTs/VS2 CE.